2015
DOI: 10.1037/xge0000031
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of seven hypotheses for metamemory performance in rhesus monkeys.

Abstract: Knowing the extent to which nonhumans and humans share mechanisms for metacognition will advance our understanding of cognitive evolution and will improve selection of model systems for biomedical research. Some nonhuman species avoid difficult cognitive tests, seek information when ignorant, or otherwise behave in ways consistent with metacognition. There is agreement that some nonhuman animals “succeed” in these metacognitive tasks, but little consensus about the cognitive mechanisms underlying performance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
81
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 65 publications
6
81
0
Order By: Relevance
“…This includes generalizing the use of the UR across a size discrimination task, a brightness discrimination task, an arch-length discrimination task, a line orientation discrimination task, a metamemory task, and a prospective metamemory task. The monkeys successfully transferred the use of the UR across the tasks, this transfer was observed in the first test session, and the UR-transfer was more successful across successive task exposures (also see Basile et al, 2015). Results from monkeys (A) Lou and (B) Murph in a task with variable numbers of rewards at risk and the need to make a density discrimination.…”
Section: Successes In Animal Metacognition Tests -Primarily Primatesmentioning
confidence: 99%
See 2 more Smart Citations
“…This includes generalizing the use of the UR across a size discrimination task, a brightness discrimination task, an arch-length discrimination task, a line orientation discrimination task, a metamemory task, and a prospective metamemory task. The monkeys successfully transferred the use of the UR across the tasks, this transfer was observed in the first test session, and the UR-transfer was more successful across successive task exposures (also see Basile et al, 2015). Results from monkeys (A) Lou and (B) Murph in a task with variable numbers of rewards at risk and the need to make a density discrimination.…”
Section: Successes In Animal Metacognition Tests -Primarily Primatesmentioning
confidence: 99%
“…Yet again, humans ( Figure 2A) and monkeys ( Figure 2B) displayed an increase in the use of the UR corresponding with a decrease in use of the categorization responses for the most difficult trials. Other experiments explored metacognition in rhesus monkeys and showed that the use of the UR or other metacognitive responses transfers across a variety of different tasks (Basile, Schroeder, Brown, Templer, & Hampton, 2015;Brown, Templer, & Hampton, 2017;Kornell, Son, & Terrace, 2007;Smith, Redford, Beran, & Washburn, 2010;Templer & Hampton, 2012) and that monkeys will continue using the UR when feedback is delayed (Smith, Beran, Redford, & Washburn, 2006), minimizing the likelihood that task-specific environmental cues are responsible for the use of the UR. Figure 1. A.…”
Section: Successes In Animal Metacognition Tests -Primarily Primatesmentioning
confidence: 99%
See 1 more Smart Citation
“…In monkeys and rats, some studies have also developed a "play it again paradigm". Monkeys had to recall and reproduce the location of two squares on a touchscreen, but the target stimuli were no longer visible during the response period (macaques and baboons: Basile et al, 2015;Malassis et al, 2015). In rats, the subjects had to classify a brief noise as short or long (Foote and Crystal, 2012).…”
Section: Evaluation Of Metacognitive Control: the Hint-seeking Paradigmmentioning
confidence: 99%
“…The advances in research on metacognition in monkeys (e.g. Basile et at., 2015) and apes (e.g. Call & Carpenter, 2001) may be used to design experiments to test for metacognitive abilities in cows.…”
mentioning
confidence: 99%